Are Newer Antiseizure Medications Better Off in Maintaining Oral Health in Persons with Epilepsy? - Jayakumari Nandana; Jithin George; Lakshmi Priya; Thania E Pidiyancheril; KY Manisha; Ramshekhar N Menon; Ashalatha Radhakrishnan (Annals of Indian Academy of Neurology)
Background and Objectives: Persons with epilepsy (PWE) have poor dental hygiene, contributed by the severity of epilepsy, ignoring oral health, and the medications used. A continuing need exists for a better understanding of the effects of antiseizure medications (ASMs) on oral health. Several studies have shown the effects of older ASMs on oral health, but there is a lack of those exploring oral side effects of newer ASMs. Methods: A cross-sectional study was conducted in which 69 PWE on ASMs were compared with 33 controls. A structured questionnaire was used to collect data on demographics, oral hygiene practices, and medication history including use of older and newer ASMs. Dental examination along with plaque, gingival, Decayed, Missing, and Filled Teeth (DMFT), and Decayed, Missing, and Filled teeth Surface (DMFS) indices were assessed. PWE were divided into three groups based on whether they were on older ASMs, newer ASMs, or a combination of both. Data was statistically analyzed. Results: PWE have poor dental health with significantly higher gingival index, plaque index, calculus, DMFS, and DMFT scores compared to controls (P < 0.001). Concerning ASMs, patients on older ASMs had poor dental health with higher gingival index, gingivitis, and periodontitis compared to those on newer ASMs (P < 0.005). Patients on polytherapy tended to have worse periodontal parameters. Gingival hyperplasia was common in patients taking phenytoin alone compared to those taking folic acid along with phenytoin (P < 0.05). Conclusion: Older ASMs, especially phenytoin, can be associated with significant oral side effects. Newer ASMs are relatively safe, but further research is needed to fully understand their long-term effects.